2010
DOI: 10.1177/0267659110392441
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch replacement with moderate hyperthomia and a modified 3-pump circuit

Abstract: A strategy employing moderate hypothermia for replacement of the aortic arch is proposed to avoid the complications of profound hypothermic circulatory arrest. Two patients underwent complete replacement of the aortic arch using three pumps (Figure 1a - one to perfuse the brain, one for the thoracoabdominal aorta and the third for the heart). There were no complications and the patients were extubated uneventfully. The method preserves autoregulation of cerebral blood flow without high vascular resistances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…However the lack of end organ dysfunction and apparent early correction of acidosis suggests a potential protective effect. Our results utilizing this modified perfusion strategy demonstrate similar benefits as those described by other groups: Matalanis et al, 13 Matsuyama et al, 12 Charumathi et al 14 The step-wise distal anastomosis technique and the cerebral and visceral protection demonstrated faster rewarming and decreased CPB times. 12 In their large series of 119 patients undergoing total arch replacement, Matsuyama et al utilized a separate lower body perfusion and demonstrated excellent clinical outcome and improved operative mortality from 10.4% to 3.4% when they started utilizing this technique.…”
Section: Discussionsupporting
confidence: 87%
“…However the lack of end organ dysfunction and apparent early correction of acidosis suggests a potential protective effect. Our results utilizing this modified perfusion strategy demonstrate similar benefits as those described by other groups: Matalanis et al, 13 Matsuyama et al, 12 Charumathi et al 14 The step-wise distal anastomosis technique and the cerebral and visceral protection demonstrated faster rewarming and decreased CPB times. 12 In their large series of 119 patients undergoing total arch replacement, Matsuyama et al utilized a separate lower body perfusion and demonstrated excellent clinical outcome and improved operative mortality from 10.4% to 3.4% when they started utilizing this technique.…”
Section: Discussionsupporting
confidence: 87%
“…Continuous ACP was maintained throughout the period of CPB at a temperature of 25 C. Flows varied between 1 and 3 lpm depending on whether flow was directed to the axillary artery and continued bihemispherically through the left common carotid artery at first and later the anastomosed graft using a mean perfusion pressure of 50-70 mmHg as a guide (2,14). A mild hypothermia (28-32 C) strategy avoids the effects of deep hypothermia and may help to decrease transfusion volume and reduce duration of intubation and intensive care unit stay (7,8). Others suggest that safety margins may be jeopardized with the mild hypothermia approach and a moderate hypothermia strategy may be better (7,8,15).…”
Section: Discussionmentioning
confidence: 99%
“…A mild hypothermia (28-32 C) strategy avoids the effects of deep hypothermia and may help to decrease transfusion volume and reduce duration of intubation and intensive care unit stay (7,8). Others suggest that safety margins may be jeopardized with the mild hypothermia approach and a moderate hypothermia strategy may be better (7,8,15). The optimal perfusion temperature and ACP flow rates have not yet been clearly defined in the literature (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations